2007
DOI: 10.1289/ehp.9499
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Particulate Matter (PM 2.5–10 ) Affects Heart Rate Variability, Blood Lipids, and Circulating Eosinophils in Adults with Asthma

Abstract: IntroductionWe investigated whether markers of airway and systemic inflammation, as well as heart rate variability (HRV) in asthmatics, change in response to fluctuations in ambient particulate matter (PM) in the coarse [PM with aerodynamic diameter 2.5–10 μm (PM2.5–10)] and fine (PM2.5) size range.MethodsTwelve adult asthmatics, living within a 30-mile radius of an atmospheric monitoring site in Chapel Hill, North Carolina, were followed over a 12-week period. Daily PM2.5–10 and PM2.5 concentrations were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 57 publications
(68 reference statements)
7
84
2
Order By: Relevance
“…This could help explain some of the previously negative study findings. 116 Similarly, coarse particulates between 0.25 and 1.0 m in diameter may affect the cardiovascular system, 221,264,265 and although the available data related to hard events and cardiovascular mortality have suggested a relationship, 265,266 recent findings have been less consistent. 104 In the most recent time-series analysis of 112 US cities, coarse PM was independently associated with elevated all-cause, stroke, and pulmonary, but not cardiovascular, mortality after controlling for PM 2.5 .…”
Section: Additional Epidemiological Findings and Areas Of Continued Rmentioning
confidence: 99%
“…This could help explain some of the previously negative study findings. 116 Similarly, coarse particulates between 0.25 and 1.0 m in diameter may affect the cardiovascular system, 221,264,265 and although the available data related to hard events and cardiovascular mortality have suggested a relationship, 265,266 recent findings have been less consistent. 104 In the most recent time-series analysis of 112 US cities, coarse PM was independently associated with elevated all-cause, stroke, and pulmonary, but not cardiovascular, mortality after controlling for PM 2.5 .…”
Section: Additional Epidemiological Findings and Areas Of Continued Rmentioning
confidence: 99%
“…A panel study of 12 adult asthmatics residing in Chapel Hill, North Carolina, reported associations between HRV, blood lipids, and circulating eosinophils and coarse, but not fine, PM (Yeatts et al 2007).…”
mentioning
confidence: 99%
“…A study among asthmatic patients showed that with a 1-microg/m3 increase in coarse PM, triglycerides increased 4.8% (p = 0.02), and very low-density lipoprotein increased 1.15% (p = 0.01). This study suggested that small temporal increases in ambient coarse PM are sufficient to affect lipid profile in adults with asthma (Yeatts et al, 2007). Hypercholesterolemia may potentiate diesel exhaust-related endothelial gene regulation.…”
Section: Impact Of Climate Change and Air Pollution On Dyslipidemia Amentioning
confidence: 72%